Evaluating Circadian Oscillators in Cancer Stem Cells - E. Geusz, Michael; P. Sharma, Vishal; Sarma, Ashapurna; Malik, Astha (Journal of Evolving Stem Cell Research, 2015)
Cancer is influenced by the ability of cells to maintain circadian rhythms in molecular and metabolic processes. Disturbance of the underlying circadian timing mechanism in circadian clock cells leads to a higher frequency and more rapid progression of cancer. Cancer stem cells with properties of embryonic and somatic stem cells have been implicated as tumor initiators in several types of cancers. Although tumors are reported to have disorganized circadian rhythms, evidence of in vitro circadian rhythms in cancer stem cells of gliomas was recently presented. The possibility and consequences of circadian clocks functioning in cancer stem cells within tumors is examined, and the possible benefits to these cells from circadian timing is discussed in relation to cancer treatments.
Keywords: cancer stem cell; circadian rhythm; chronotherapy; tumorigenesis